The Relationship between Mother's Knowledge and Attitudes and the Incidence of Young Marriage in the West Martapura Region - Yuliastuti, Erni; Safitri, Khairunnisa; Hipni, Rubiati (Midwifery Departement Poltekkes Kemenkes Banjarmasin, 2023)
Results of the 2007 Indonesian Population Data Survey (IDHS) the number of cases of early marriage in Indonesia reached 50 million people with an average age of marriage 19.1 years. Data from the Office of the Ministry of Religion of South Kalimantan Province shows that the highest cases of early marriage occurred in Banjar Regency, with 7,346 cases of early marriage. In the West Martapura Region, there was an increase in young marriages from 2015 (24.6%) to 2016 (35.8%). This study aims to determine the relationship between knowledge and attitudes of mothers with the incidence of young marriage in the West Martapura Region in 2017. The research method used is an analytical survey with a cross sectional approach. The total population is 65 mothers and the total sample is 56 mothers who married young in 2016. The sampling technique used is simple random sampling. The research instrument used daily marriage registers and questionnaires directly to mothers who were recorded as having married at a young age in the West Martapura Region in 2016. Data analysis was carried out using the Chi-Square test with a 95% confidence level. Statistical test results using Chi Square obtained ρ= 0.026 <α=0.05 meaning that there is a relationship between mother's knowledge and young marriage and for the relationship between mother's attitude and young marriage the result is ρ= 0.014 <α=0.05 meaning that there is a relationship between attitude mother with young marriage. The conclusion of this study is that there is a relationship between knowledge and attitudes of mothers with the incidence of young marriage.